Hypertension prevalence in human coronavirus disease: the role of ACE system in infection spread and severity - Gaetano Ruocco; Mauro Feola; Alberto Palazzuoli (International Journal of Infectious Diseases, 2020)
The prevalence of hypertension is high in patients affected by coronavirus disease 2019 (COVID-2019) and it appears to be related to an increased risk of mortality, as shown in many epidemiological studies. The angiotensin-converting enzyme (ACE) system is not uniformly expressed in all of the human races, and current differences could explain some of the geographical discrepancies in infection around the world. Furthermore, animal studies have shown that the ACE2 receptor is a potential pathway for host infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19. As two-thirds of hypertensive patients take ACE inhibitors/angiotensin receptor blockers, several concerns have been raised about the detrimental role of current antihypertensive drugs in COVID-19. This report summarizes the recent evidence for and against the administration of ACE blockade in the COVID-19 era.